The Effect of Self-Confidence and Independence of Learning on Students' Mathematics Learning Outcomes - Murnaka, Nerru Pranuta; Kiat, Selvi; Rahman, Bobbi; Indira, Elizabeth Wahyu Margareth; Siminto, Siminto (Universitas Wiralodra, 2023)
Self-confidence and learning independence are internal factors that influence student learning outcomes. Because both of them demand students in total to be able to take responsibility for students related to the learning process. This study aims to investigate whether there is a significant effect of self-confidence and learning independence on students' mathematics learning outcomes. This research is a quantitative research with a correlational design type. The population in this study were all students of class VII MTs Negeri 5 Tangerang with a sample of 132 students and the sample technique used was simple random. The instruments used in this study were questionnaires and math learning outcomes test questions. Questionnaires are used to measure self-confidence and student learning independence. While the test is used to measure students' mathematics learning outcomes. Based on the results of the self-confidence regression test on student learning outcomes, the sig. 0.026 <0.05, meaning that there is a significant influence between self-confidence and student learning outcomes. Then for the results of the independent learning regression test on student learning outcomes, the sig value was obtained. 0.672 > 0.05, which means that there is no significant effect of independent learning on student learning outcomes. While the results of the regression test of self-confidence and learning independence on student learning outcomes, the sig. 0.084, which means that there is no significant effect of self-confidence and learning independence on students' mathematics learning outcomes.